Six-minute walk distance, ECOG Performance Status, and Modified Borg Scale scores in a cohort of Pakistani men and women with noncancerous end-stage liver disease selected for liver transplant - Khaula Ashraf; Saeed Bin Ayaz; Rehana Yasmeen; Bisharat Ullah Khan; Rabia Fayyaz; Naureen Tassadaq (Journal of the Pakistan Medical Association, 2021)
Objectives: To evaluate the functional status of Pakistani patients with non-cancerous end-stage liver disease selected for liver transplant, and to compare results acquired through various assessment tools. Methods: The study was conducted at the Rehabilitation Medicine Department, Shifa International Hospital, Islamabad, Pakistan, from August 2017 to November 2019, and comprised end-stage liver disease patients of either gender who had been selected for liver transplant. Assessment tools included the Six-Minute Walk Distance, Eastern Cooperative Oncology Group Performance Status and Modified Borg Scale across age, gender, ethnicity, primary aetiology, and Model for end-stage liver disease scores. Data was analysed using SPSS 20. Results: Of the 172 patients, 143(83%) were males; 99(58%) hailed from the Punjab province; and 118(71%) had hepatitis C as the most common aetiology. The overall mean age was 46.1±10.5 years (range: 14–70 years). The mean Six-Minute Walk Distance was 291.9±67.2m. Model for end-stage liver disease scores had a significant inverse correlation with Six-Minute Walk Distance (p<0.01) and a significant positive correlation with Modified Borg Scale (p=0.02) and Eastern Cooperative Oncology Group Performance Status scores (p<0.01). Age and ethnicity had no correlation with the variables (p>0.05). Conclusions: The Six-Minute Walk Distance score was significantly low. The Model for end-stage liver disease scores were inversely correlated with Six-Minute Walk Distance scores, and positively correlated with Eastern Cooperative Oncology Group Performance Status and Modified Borg Scale scores. Continuous...